UNAVOIDABLE CLASHES: EXPLORING THE IMPLICATIONS OF A CHINA-RUSSIA ALLIANCE ON GLOBAL GEOPOLITICS - Yakhshilikov, Sanjar (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2023)
The current relations between China and Russia are the result of the rapprochement policies of both countries. Shared fears about US hegemony, mutual economic benefits, and strong links between Xi Jinping and Vladimir Putin escalated Sino-Russia relations into a new stage. Russia needs regional security in Southeast Asia, and even though the strategic interests of China and Russia do not match over the region, they are both eager to contain the US. Recent Russia – Ukraine border issues are well-matched with China – Taiwan issues that also make the states feel mutuality between them. The results of the two issues may be the same. Moscow is making sure as time goes by that rapprochement with the West is impossible, Russia is going to suffer from economic sanctions, and the West has already begun decoupling. Despite all of the partnerships and mutuality, China and Russia are still not allies. The inactive confrontations between the two outnumber all of the abovementioned positives.